PRL-3 and MMP9 Expression and Epithelial-Mesenchymal Transition Markers in Circulating Tumor Cells From Patients With Colorectal Cancer: Potential Value in Clinical Practice - Hong, Xiao-Cui; Liang, Qi-Lian; Chen, Man; Yang, Hai-Xia; Huang, Jie; Yi, Si-Lin; Wang, Zhen-Wei; Liang, Hai-Yan; Zhang, Ding-Yue; Huang, Zeng-Yi (Frontiers in Oncology, 2022)
Objective: To evaluate the clinical correlation of epithelial-mesenchymal transition (EMT) with PRL-3 and MMP9 expression in the circulating tumor cells (CTCs) of patients with colorectal cancer (CRC). Materials and Methods: Between January 2016 and December 2018, the EMT phenotype-based subsets of CTCs and the expression levels of PRL-3 and MMP9 in CTCs were identified, and their clinical values in 172 patients were evaluated. The CTCs were isolated, classified, and counted using the CanPatrolTM CTC filtration system. The CTC subsets (epithelial cells, mesenchymal cells and biphenotypic cells), as well as PRL-3 and MMP9 expression, were detected by RNA in situ hybridization. Results: CTCs were detected in 93.0% (160/172) of the included patients with CRC. Positive PRL-3 and MMP9 expression in CTC and M-CTC was found in 75.0% (102/136) and 80.8% (97/120) of the patients, respectively. The proportion of patients with positive PRL-3 and MMP9 expression in M-CTC was significantly associated with distant metastasis (p<0.05). The patients with ≥6 CTCs tended to show poorer progression-free survival (PFS) and overall survival (OS) rates (p=0.016, 0.02, respectively), and the patients with ≥3 M-CTC also showed poor PFS (p=0.0013). Additionally, the patients with positive PRL-3 and MMP9 expression in CTCs had significantly poorer PFS (p=0.0024) and OS (p=0.095) than the patients with negative PRL-3 and MMP9 expression. Multivariate Cox analysis uncovered that positive PRL-3 and MMP9 expression in CTCs may be an independent prognostic factor for worse PFS. Conclusion: EMT phenotypes and CTC numbers can be used as prognostic indicators for metastasis and survival in patients with CRC, and the combination of PRL-3 and MMP9 expression in CTCs is a promising clinical marker for patients with CRC.